GM-CSF: An immune modulatory cytokine that can suppress autoimmunity. Issue 2 (October 2015) - Bhattacharya, Palash; Thiruppathi, Muthusamy; Elshabrawy, Hatem A.; Alharshawi, Khaled; Kumar, Prabhakaran; Prabhakar, Bellur S.
Highlights: GM-CSF is an established growth and differentiation factor for multiple cell lineages. The role of GM-CSF in steady state myelopoiesis appears to be redundant. GM-CSF has an additional role in the modulation of myeloid cell functions. Immune modulatory role of GM-CSF determines the outcome of many autoimmune diseases. We review literature to discuss of the role of GM-CSF in immune tolerance. Abstract: GM-CSF was originally identified as a colony stimulating factor (CSF) because of its ability to induce granulocyte and macrophage populations from precursor cells. Multiple studies have demonstrated that GM-CSF is also an immune-modulatory cytokine, capable of affecting not only the phenotype of myeloid lineage cells, but also T-cell activation through various myeloid intermediaries. This property has been implicated in the sustenance of several autoimmune diseases like arthritis and multiple sclerosis. In contrast, several studies using animal models have shown that GM-CSF is also capable of suppressing many autoimmune diseases such as Crohn's disease, Type-1 diabetes, Myasthenia gravis and experimental autoimmune thyroiditis. Knockout mouse studies have suggested that the role of GM-CSF in maintaining granulocyte and macrophage populations in the physiological steady state is largely redundant. Instead, its immune-modulatory role plays a significant role in the development or resolution of autoimmune diseases. This is mediated either through the differentiation of precursor cells into specialized non-steady state granulocytes, macrophages and dendritic cells, or through the modulation of the phenotype of mature myeloid cells. Thus, outside of myelopoiesis, GM-CSF has a profound role in regulating the immune response and maintaining immunological tolerance.